Experimental and Numerical Studies on Vertical Properties of a New Multi-Dimensional Earthquake Isolation and Mitigation Device - Zhaodong Xu; Liheng Lu; Benqiang Shi; Fuhgwo Yuan (Shock and Vibration)
When designing critical structures such as long-span structures and high-rise buildings, earthquake excitation in the vertical direction, in addition to the horizontal direction, should also be taken into consideration. Study on new devices that can mitigate and isolate multi-dimensional (including both horizontal and vertical) earthquake actions has a remarkable significance. A new kind of multi-dimensional earthquake isolation and mitigation device was recently developed, and experimental study on vertical performances of the device under different excitation frequencies and amplitudes has been carried out in this paper. The characteristics of the vertical properties including the initial stiffness, the energy dissipation stiffness, the energy dissipation per cycle and the vertical damping ratio changing with excitation frequency and amplitude were studied, and the formulas describing the characteristics were proposed. It can be concluded that the initial stiffness and the energy dissipation stiffness increase slightly with increasing frequency, while the energy dissipation per cycle and the damping ratio decrease slightly with increasing frequency, the initial stiffness, the energy dissipation stiffness and the damping ratio will decrease slightly with increasing excitation amplitudes, and the proposed formulas can describe the vertical properties of the multi-dimensional earthquake isolation and mitigation device changing with excitation frequency and amplitude.